Applicablity of virtual private networks (VPN) in enterprises - Zhou, Qiang. (2008)
The purpose of this project is to investigate the applicability of VPN in enterprises and possible implementation schemes. This report will begin with discussion on the characteristics of VPNs in general and the different types of VPN available in the market. This is followed by a brief discussion on the security aspects of VPNs.